Is the Jump-Diffusion Model a Good Solution for Credit Risk Modeling? The Case of Convertible Bonds - Tim Xiao (International Journal of Financial Markets and Derivatives, 2015)
This paper argues that the reduced-form jump diffusion model may not be appropriate for credit risk modeling. To correctly value hybrid defaultable financial instruments, e.g., convertible bonds, we present a new framework that relies on the probability distribution of a default jump rather than the default jump itself, as the default jump is usually inaccessible. As such, the model can back out the market prices of convertible bonds. A prevailing belief in the market is that convertible arbitrage is mainly due to convertible underpricing. Empirically, however, we do not find evidence supporting the underpricing hypothesis. Instead, we find that convertibles have relatively large positive gammas. As a typical convertible arbitrage strategy employs delta-neutral hedging, a large positive gamma can make the portfolio highly profitable, especially for a large movement in the underlying stock price.
Keywords: 330; jump diffusion; convertible bond; convertible underpricing; convertible arbitrage; default time approach; default probability approach; asset pricing; credit risk modeling